2021
DOI: 10.1152/ajplung.00528.2020
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3-like-1 protects airway function despite promoting type 2 inflammation during fungal-associated allergic airway inflammation

Abstract: Exposure to fungi can result in a wide range of comorbidities depending on the immune status of the host. Chronic exposure and reactivity to fungi such as Aspergillus fumigatus can result in conditions such as severe asthma with fungal sensitization (SAFS) or allergic bronchopulmonary aspergillosis (ABPA). However, the pathophysiology of SAFS and ABPA are not well understood. Here, we report that the chitinase-like protein YKL-40 is elevated in lung lavage fluid from human asthmatics that are sensitized to fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 70 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…Examples of the former include studies from our laboratory and others that demonstrated that CHI3L1 inhibits hyperoxia-induced acute lung injury (41,74,75), is a JCI Insight 2021;6(21):e148749 https://doi.org/10.1172/jci.insight.148749 powerful inhibitor of cellular apoptosis (39), and controls bacterial infection via the regulation of inflammasome activation (76). Our studies demonstrated that CHI3L1 is a potent stimulator of type 2 inflammation, M2 macrophage differentiation, and tissue remodeling and that CHI3L1 excess is a major contributor to these responses in allergic and fibrotic disorders (39,67,77,78). The present studies highlight the importance of CHI3L1 as a stimulator of ACE2 and SPP and demonstrate that these inductive events enhance tissue inflammation and injury in COVID-19.…”
Section: Discussionsupporting
confidence: 63%
“…Examples of the former include studies from our laboratory and others that demonstrated that CHI3L1 inhibits hyperoxia-induced acute lung injury (41,74,75), is a JCI Insight 2021;6(21):e148749 https://doi.org/10.1172/jci.insight.148749 powerful inhibitor of cellular apoptosis (39), and controls bacterial infection via the regulation of inflammasome activation (76). Our studies demonstrated that CHI3L1 is a potent stimulator of type 2 inflammation, M2 macrophage differentiation, and tissue remodeling and that CHI3L1 excess is a major contributor to these responses in allergic and fibrotic disorders (39,67,77,78). The present studies highlight the importance of CHI3L1 as a stimulator of ACE2 and SPP and demonstrate that these inductive events enhance tissue inflammation and injury in COVID-19.…”
Section: Discussionsupporting
confidence: 63%
“…Our laboratory focuses on immunopathogenic versus immunoprotective mechanisms during fungal-associated allergic airway inflammation (fungal asthma). Regarding the latter, we have identified CX3CL1/fractalkine as an immunoprotective mediator during fungal asthma ( 41 ) as well as the chitinase-like protein BRP-39 (YKL-40 in humans), although BRP-39 protected the lung during fungal asthma in a yet to be defined nonimmune manner ( 19 ). In contrast, we have identified IL-7 ( 18 ) and IL-1R signaling ( 17 ) as immunopathogenic factors during fungal asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cells were isolated via bronchoalveolar lavage (BAL) as previously described ( 19 ). Cells were washed, and Fc receptors were blocked with Mouse BD Fc Block (BD Biosciences) at 4°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that the ECs expressed certain chemotaxis-associated genes, such as Cxcl12, which may further facilitate leukemia cell migration and proliferation. 30 Furthermore, the expression of inflammation-and leukemogenesis-related genes, such as Chil1, [31][32][33] Atf3, 34 and Itgb2, 35 was upregulated in quiescent leukemia cells after chemotherapy (Fig. 4D).…”
Section: Transcriptomic Characteristics Of Ecs and Resting Leukemia C...mentioning
confidence: 96%